Optimization of hemp seed supplementation with phytobiotics in laying hen feed to improve egg yolk fatty acids, tocopherols and cholesterol using response surface models - Youssef Rbah; Yassine Taaifi; Aymane Allay; Farid Mansouri; Farid Mansouri; Kamal Belhaj; Nadia Houmy; Abdelaaty A. Shahat; Omar M. Noman; Othmane Merah; Embarek Azeroual; Reda Melhaoui; et al. (Frontiers in Sustainable Food Systems)
IntroductionEnriching egg yolks with n-3 polyunsaturated fatty acids (n-3 PUFAs) enhances their nutritional value. While phytobiotics like hemp seed, turmeric, and black pepper show potential for this purpose, their optimal dietary inclusion levels in laying hens remain insufficiently studied.MethodsThis study employed a Box-Behnken Design (BBD) to evaluate the effects of dietary supplementation with hemp seed, turmeric, and black pepper on the enrichment of egg yolks in laying hens. A total of 570 hens were divided into 19 treatment groups, 18 according to the BBD and one control group. The primary responses measured included the contents of saturated fatty acids (SFAs), n-3 PUFAs, n-6 PUFAs, the n-6/n-3 ratio, cholesterol, and total tocopherols in egg yolks.ResultsAll models showed statistically significant results (p < 0.05), with coefficients of correlation (R2) ranging from 0.80 to 0.90. Response surface analysis and Pareto charts indicated that dietary hemp seed and black pepper significantly influenced all measured parameters, while turmeric primarily affected cholesterol levels in combination with hemp seed. Ridge optimization analysis identified optimal outcomes at 27.05% SFAs, 5.86% n-3 PUFAs, a 6.04 n-6/n-3 ratio, 846.55 μg/g tocopherols, and 7.02 mg/g cholesterol. The best combination was determined to be 30% hemp seed, 3% turmeric, and 0.3% black pepper.ConclusionThis study demonstrates that BBD and response surface methodology are effective tools for optimizing functional feed ingredient levels. The results strongly encourage the development of enriched eggs with improved quality and nutritional properties, contributing to a sustainable and healthier poultry product.